Remediation of cadmium-tolerant bacteria combined with plant absorption on soil heavy metal cadmium pollution - ZHOU Huifang; WANG Jingwen; SUN Jilin; LI Dan; ZHANG Qichun (浙江大学学报. 农业与生命科学版)
Heavy metal contaminants enter the environment through various means, causing heavy metal pollution in the soil, especially heavy metals in farmland soils, which are becoming increasingly serious. Microorganisms, especially bacteria have a large surface area, are charged and have strong metabolic activity, and play a unique role in remediation of heavy metal-contaminated soil. The cadmium- tolerant strain m6, isolated from cadmium- polluted soil by our lab, has a strong ability to enhance the mobility and bioavailability of heavy metals in soils. Ordinary surfactants also can activate heavy metals and improve the migration and bioavailability of heavy metals in soils, and have a positive effect on the removal of heavy metals in contaminated soils and sediments. In our previous study, a heavy metal adsorbent Beiyang rod (BY rod) was set up, which can adsorb heavy metals including mercury, zinc, cadmium and copper in soils. Therefore, the objective of the present work was to study the remediation effect of cadmium-tolerant strains or surfactants combined with plant absorption and BY rod on soil heavy metal cadmium (Cd) pollution.The BY rod combined with cadmium-tolerant bacteria m6 or surfactant was conducted in a field experiment, including CK, T1 (BY rod treatment), T2 (BY rod plus cadmium- tolerant bacteria treatment) and T3 [BY rod plus sodium dodecyl benzene sulfonate (SDBS) treatment]. Moreover, three species of hyperaccumulator (Sedum plumbizincicola, Sedum emarginatum Migo and Sedum alfredii) combined with cadmium-tolerant strain m6 (S1 treatment) or surfactant (S2 treatment) were set in a pot experiment. Both the field experiments and pot experiments were carried out in the greenhouses in Fuyang District, Zhejiang Province. The activities of soil urease, protease, phosphatase and dehydrogenase were measured by phenol-sodium hypochlorite colorimetric method, copper salt colorimetric method, triphenyltetrachloride azole (TTC) and benzodiazepine colorimetric method, respectively.The results showed that the BY rod combined with cadmium-tolerant bacteria m6 or surfactant had higher absorption of the active cadmium than the control treatment. The cadmium- tolerant bacteria m6 and surfactants could significantly increase the content of available cadmium, enzyme activity and microbial quantity in the soil, while the effects as sodium dodecyl benzene sulfonate (SDBS) > cadmium- tolerant bacteria m6. The reduction of the available cadmium concentration in the soil was the highest under the S. plumbizincicola treatment, and the absorbed concentrations of Cd and Zn in the S. plumbizincicola were significantly higher than those in the S. emarginatum and S. alfredii. After the potentially available cadmium in the soil was converted to activation state of cadmium, it could be absorbed by BY rod or cultivated plants. It was also revealed that the Cd concentration absorbed by S. plumbizincicola was higher than that by S. emarginatum and S. alfredii in the experiment of three kinds of sedum combined with cadmium- tolerant bacteria for remediation, and the soil enzyme activity and the abundance of microorganisms were higher after the remediation by S. plumbizincicola.It is concluded that the combination of cadmium- tolerant bacteria and S. plumbizincicola is a feasible and effective remediation method for soil cadmium pollution.